2015
DOI: 10.1016/j.ajog.2014.09.032
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum care for mothers diagnosed with hepatitis B during pregnancy

Abstract: Objective To determine rates of maternal postpartum hepatitis B virus (HBV) follow-up with a HBV specialist and identify factors associated with poor follow-up, as prior research has focused on infant outcomes and not maternal care. Study Design We conducted a retrospective review of data from Partner’s HealthCare system, the largest health care system in Massachusetts, and identified women with chronic HBV who delivered from 2002 to 2012. Results We identified 291 women (mean age 31.5 years, 51% Asian) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 24 publications
1
6
0
1
Order By: Relevance
“…MTCT of HBV can occur at three stages of pregnancy: intrauterine, intrapartum or postpartum, and the risk for MTCT of HBV increases with high maternal viral load, positive HBeAg status, preterm labour, prolonged labour and failure of immunoprophylaxis in siblings [10, 11]. The current standard of care for the prevention of MTCT of HBV infection includes an active and passive immunoprophylaxis with HBV immunoglobulin and vaccination administered immediately after birth to neonates of HBsAg positive mothers, and referral of mothers to hepatology clinics for assessment and follow up [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…MTCT of HBV can occur at three stages of pregnancy: intrauterine, intrapartum or postpartum, and the risk for MTCT of HBV increases with high maternal viral load, positive HBeAg status, preterm labour, prolonged labour and failure of immunoprophylaxis in siblings [10, 11]. The current standard of care for the prevention of MTCT of HBV infection includes an active and passive immunoprophylaxis with HBV immunoglobulin and vaccination administered immediately after birth to neonates of HBsAg positive mothers, and referral of mothers to hepatology clinics for assessment and follow up [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…However, not all women who are found to have HBV during pregnancy are referred to specialized care for follow-up care of their hepatitis, despite current recommendations (ACOG 2007). A retrospective study at Partners HealthCare system, the largest healthcare system in Massachusetts, found that 47% of women diagnosed with HBV perinatally had follow-up with an HBV specialist, but only 19% had appropriate HBV-related laboratory tests within 1 year of their HBV diagnosis (Chang 2015). A subsequent analysis of the Massachusetts Virtual Epidemiologic Network, a statewide surveillance database, showed that postpartum maternal HBV follow-up laboratory testing occurred in 50% of Massachusetts women — higher than previously estimated but nonetheless suboptimal (Chang 2016).…”
Section: Introductionmentioning
confidence: 99%
“…20 A single US centre found that 19% of CHB mothers received appropriate HBV care post-partum. 21 Our study uniquely interviewed these women in the post-partum phase to assess directly quality of care provided for CHB mothers and their babies against benchmark guidelines regarding maternal disease assessment and administration of IPT.…”
Section: Discussionmentioning
confidence: 99%